Tetrodotoxin infusions into the dorsal hippocampus block non-locomotor place recognition - Klement, Daniel; Past'alková, Eva; Fenton, André A (Hippocampus, 2005)
The hippocampus is critical for navigation in an open field. One component of this navigation requires the subject to recognize the target place using distal cues. The experiments presented in this report tested whether blocking hippocampal function would impair open field place recognition. Hungry rats were trained to press a lever on a feeder for food. In Experiment 1, they were passively transported with the feeder along a circular trajectory. Lever pressing was reinforced only if the feeder was passing through a 60 degrees -wide sector. Thus, rats preferentially lever pressed in the vicinity of the reward sector indicating that they recognized its location. Tetrodotoxin (TTX) infusions aimed at the dorsal hippocampi caused rats to substantially increase lever pressing with no preference for any region. The aim of Experiment 2 was to determine whether the TTX injections caused a loss of place recognition or a general increase of lever pressing. A separate group of rats was conditioned in a stationary apparatus to press the lever in response to a light. The TTX injections did not abolish preferential lever pressing in response to light. Lever pressing increased less than half as much as the TTX-induced increase in Experiment 1. When these animals with functional hippocampi could not determine the rewarded period because the light was always off, lever pressing increased much more and was similar to the TTX-induced increase in Experiment 1. We conclude that the TTX inactivation of the hippocampi impaired the ability to recognize the reward place.
Keywords: Tetrodotoxin; stravovací zvyklosti; chování zvířat; Space Perception; paměť; Orientation; krysa rodu Rattus; Hippocampus; zvířata; Anesthetics, Local; hipokampus; Memory Disorders; Rats, Long-Evans; tetrodotoxin; Male; orientace; anestetika lokální; potkani Long-Evans; Rats; Memory; Animals; mužské pohlaví; Feeding Behavior; poruchy paměti; Disease Models, Animal; Behavior, Animal; vnímání prostoru; modely nemocí na zvířatech